Neural effects of a single dose of fluoxetine on resting-state functional connectivity in adolescent depression. (December 2020) - Capitão, Liliana P; Chapman, Robert; Filippini, Nicola; Wright, Lucy; Murphy, Susannah E; James, Anthony; Cowen, Phil J; Harmer, Catherine J
Fluoxetine is commonly prescribed in adolescent depression, but the neural mechanisms underlying its action remain poorly understood. Here, we used resting-state functional magnetic resonance imaging to investigate the effects of a single dose of fluoxetine vs. placebo in adolescents with major depressive disorder. In contrast with previous studies in adults that have demonstrated an acute effect of antidepressants on activity within the default mode network, a single dose of fluoxetine did not alter activity in this network in adolescent depression. There were unexpected group activity differences in the motor network, which should be clarified in future research.